Connecting habitats, boosting disease resistance: Spatial connectivity enhances amphibian microbiome defenses against fungal pathogen - Daniel Medina; Renato A. Martins; Paula R. Prist; Shannon Buttimer; Wesley J. Neely; Laura K. Schuck; Sasha E. Greenspan; Mariana L. Lyra; Patrick J. Kearns; Douglas C. Woodhams; Molly C. Bletz; Vinicius A. São-Pedro; et al. (Proceedings of the National Academy of Sciences, 2026)
Disruption of habitat connectivity alters host movement patterns and pathogen exposure in wildlife. Changes in exposure dynamics have led to increased research interest in host-associated microbial communities (i.e., microbiomes), particularly in how repeated encounters with pathogens may drive microbial filtering processes that favor the assembly of pathogen-inhibiting microbiomes, a concept known as the adaptive microbiome principle. Understanding how habitat connectivity and pathogen exposure shape adaptive microbiomes remains a key frontier in disease ecology. For widely distributed waterborne pathogens such as the amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd), sustained host exposure in contiguous terrestrial–aquatic habitats may promote selection of microbiomes with enhanced antifungal properties. In contrast, under conditions of high habitat split, where key habitats such as forests and water bodies are spatially disconnected, limited exposure to Bd during the pre-breeding and overwintering seasons may hinder the selection of Bd-inhibitory microbiomes that are critical for host protection during the subsequent breeding season, when pathogen exposure in water bodies is at its peak. Our results demonstrate that habitat split may limit recruitment of putative Bd-inhibitory skin bacteria, while Bd loads increase with habitat split for certain amphibian species. Results from Joint Species Distribution Models also indicate that habitat split is a key driver of reduced skin bacterial diversity, even after accounting for biotic and abiotic metrics. Our study provides evidence that spatial connectivity among natural habitats is essential for maintaining multiple levels of biodiversity, from host species to their associated functional microbiomes, highlighting a critical link between environmental disturbance, microbial defenses, and disease dynamics.